The Position of Dorce Gamalama Alias Dorce Ashadi's Verbal Will in the Perspective of Islamic Law - Fernanda Iqbal Fadhilah; Umar Haris Sanjaya (Qanun: Jurnal Hukum Keluarga Islam, 2025)
This research aims to analyze the position of oral testament in the perspective of Islamic law through a case study of Dorce Gamalama who wanted to be treated as a female corpse after death. This request is in the spotlight because it relates to the issue of gender identity and legal treatment of transgender people in the practice of funeral arrangements. This research is important because it concerns individual rights and the provisions of shar'i law that apply in Indonesia. The problem studied in this research is about how the position of Dorce's oral will which wants to be treated as a female corpse and whether transgender corpses are treated according to their initial gender or not in an Islamic perspective. This research uses normative legal research method with legislative approach and case approach. The sources of legal materials consist of primary, secondary, and tertiary legal materials. The data analysis technique is done qualitatively. The results show that formally, Dorce Gamalama's oral will is valid according to the Compilation of Islamic Law because it fulfills the requirements of two witnesses. However, the content of the will that contradicts the shar'i law, namely the request to be treated as a woman, is considered invalid and not required to be implemented. In Islamic law, transgender bodies are still treated according to their original gender. This research is conducted with a wise and educative fiqh approach that is needed in addressing similar issues.